Pengaruh Mikroba pada Media Kompos untuk Menanam Tanaman Johar (Senna siamea) di Pembibitan PT Asmin Bara Bronang: The Effect of Microbes on Compost Media for Growing Johar Plants (Senna siamea) at the PT Asmin Bara Bronang Nursery - Indrianto, Leonardus; Budi, Suwito Setyo; D, Rodhi Tri; D, M. Akbar Ogy; Alfarisi, Rafinoza; H, Ucok Ali M; Basuki, Bhra Jalesvianto; Bima, Farizalman Aria; Ahmad, Riza (JURNAL HUTAN TROPIKA, 2025)
Johar (Senna siamea) is a plant commonly planted in reclaimed land. It was chosen because of its ability to adapt to infertile soil conditions such as reclaimed land. Next, an experiment was conducted to plant johar plants with a planting medium of soil, compost and cocopeat plus certain fungi and microbes that are useful for accelerating growth. A total of 60 johar plants were planted in these media in polybags (30 cm x 18 cm) with the treatment of Johar A (soil: compost = 70: 30 + fungi + bacteria), johar B (soil: compost = 40: 60 + fungi + bacteria), Johar C (soil: compost: cocopeat = 1: 1: 1 + fungi) and johar D (soil: compost = 1: 1) as a control. Plants were maintained for 12 weeks and observed every week for the growth of stem height and stem diameter. The test was carried out 15 replications. The results obtained in all observations with statistical tests were not significantly different (p <0.05). The conclusion of this experiment is that this factory-made compost can be used as a growing medium for johar, so that all compost media formulas are still suitable as growing media for growing young johar plants.